Regulating HMOs: An ethical framework for cost-effective medicine - Walter M. Cadette (Levy Economics Institute of Bard College, 1998)
HMO medicine sets up an inevitable conflict between the physicians' traditional fiduciary role and the financial interests of the health plan and its physicians. Regulatory interventions, such as the formulation of rules regarding clinical practice, put government in a micromanagement role it cannot hope to perform well. Government instead should focus on building a regulatory framework to protect patients that would deal with the ethical problems that flow from the very design of HMO medicine. It should address fundamental issues, principally, the financial incentives under which HMO physicians work, restrictions on communication with patients about care options not covered by their health plan, accountability for decisions to withhold care, and the return of care decisions to the province of the physician. The challenge for regulators is to retain the power of the economic incentive to encourage cost-conscious practice, but to separate it from the welfare of patients.
Keywords: 330